2002
DOI: 10.4049/jimmunol.169.3.1159
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CD4+CD45RA+ Effector T Cells by Stimulation in the Presence of Cyclic Adenosine 5′-Monophosphate- Elevating Agents

Abstract: After TCR cross-linking, naive CD4+CD45RA+ T cells switch to the expression of the CD45RO isoform and acquire effector functions. In this study we have shown that cAMP-elevating agents added to anti-CD3- and anti-CD28-stimulated cultures of T lymphocytes prevent acquisition of the CD45RO+ phenotype and lead to the generation of a new subpopulation of primed CD4+CD45RA+ effector cells (cAMP-primed CD45RA). These cells displayed a low apoptotic index, as the presence of dibutyryl cAMP (dbcAMP)-rescued cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
(30 reference statements)
3
14
0
Order By: Relevance
“…The association of PDE4D to ␤2-adrenergic receptors resulted in desensitization of the receptors. One can speculate that PDE7A may play an important role in the development of memory T cells (35) or the regulation of activation-induced apoptosis in T lymphocytes (36) since it has been shown that cAMP is involved in these aspects of T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The association of PDE4D to ␤2-adrenergic receptors resulted in desensitization of the receptors. One can speculate that PDE7A may play an important role in the development of memory T cells (35) or the regulation of activation-induced apoptosis in T lymphocytes (36) since it has been shown that cAMP is involved in these aspects of T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, soluble CD4 and CD8 coreceptors are believed to be potent inhibitors of T-cell activation by competing with membraneanchored coreceptors, thus preventing T-cell activation via coreceptor/CD3-TCR complex-peptide/MHC interaction. 34 Better graft acceptance was observed in LT and LKT patient groups that all received a liver allograft. Therefore, HLA-G can be considered as a graft acceptance-associated marker whose expression may be up-regulated by liver factors.…”
Section: Org Frommentioning
confidence: 95%
“…It has been shown that primed CD4 ϩ T cells expressing CD45RA secreted high amounts of IL-4, IL-10, and IL-13, whereas the production of IFN-␥ was very low. 34 This pattern of cytokine production is akin to lymphocytes with a Th2 phenotype. HLA-DR ϩ cells were also overrepresented in the HLA-G-driven CD3 ϩ CD4 low and CD3 ϩ CD8 low T cells compared with CD4 high and CD8 high T cells.…”
Section: Org Frommentioning
confidence: 99%
“…Intracellular cAMP is also known as an important physiological mediator of inflammation and a key regulator of immune responses (Suárez et al, 2002).…”
Section: Introductionmentioning
confidence: 99%